Pengaruh Pelatihan Kerja Terhadap Kinerja Pramusaji Pada Departemen Food And Beverage Service Di Hotel Grand Mercure Medan Angkasa - Ardiansyah, Ichsan; Julianto, Julianto (Politeknik Pariwisata Medan, 2023)
Workplace training entails an endeavor aimed at enhancing employees' skills to attain specific benchmarks. During this process, participating employees are furnished with diverse instructions and practical guidance, enabling them to reach the desired proficiency level. The fundamental goal of this job training is to cultivate employees who can ultimately proficiently execute assigned tasks, minimizing errors, and enhancing productivity across various responsibilities. This investigation seeks to ascertain the extent of the impact of job training on the performance of servers at the Grand Mercure Hotel Medan Angkasa. Data collection was executed through a questionnaire and direct observations at the research site. The research approach utilized here is quantitative in nature. According to the results derived from the coefficient of determination test, it is evident that the influence of job training (variable X) on server performance (variable Y) amounts to 47.3%, while the remaining 52.7% is influenced by external factors beyond the scope of this study. The findings of this research underscore that job training exerts a positive and significant effect on server performance, and there exist other independent variables that impact server performance beyond the confines of this particular study.